MENINGKATKAN KEMAMPUAN MEMBACA PADA ANAK TUNARUNGU MELALUI MEDIA FLASH CARD - Elmiyanti Bangun (Universitas Negeri Padang, 2012)
This research is surface by a problem who’s found in SDLB N 20 Pondok II Pariaman, a deaf child X can not read word thing, this research have am to increase child talent in read word thing with right and exact, and see too is flash card media effective to increase read word thing talented.This research use approach experiment in single subject research (SSR) type with the research desian use A-B desian. subject of the evaluation is light deaf child x class II/B. Be based yied this research show that, talent of light deaf child in read word thing can rised by flash card media. Be based yield analiysis data research use flash card media in a repeat manner can increase talented of light deaf child class II/B. So proven hypothesis who’s sunggsted, answer if flash card media is effective in increase talented to read word thing of light deaf child X rise, so kesearcher propose to teacher for use flash card media to read word lesson furthermore